Balloon-expandable stents for native coarctation of the aorta in children and adolescents. Issue 51 (23rd December 2022) - Kasar, Taner; Erkut, Ozturk; Tanidir, İ. Cansaran; Şahin, Murat; Topkarci, M. Akin; Guzeltas, Alper
Abstract : Although balloon-expandable stent implantation for native aortic coarctation is a preferred method in the adolescent age group, there are insufficient data about indications for and the efficacy of the procedure in a younger age group. The aim of this study was to compare and evaluate the data of young pediatric and adolescent patients who underwent balloon-expandable stent implantation because of native aortic coarctation. The retrospective analysis included the demographic characteristics and data related to the procedure and follow-up of patients who underwent stent implantation for native aortic coarctation between August 2010 and November 2017. Patients with re-coarctation were excluded from the study. The patients were separated into 2 groups as the adolescent group (Group I: 10–18 years) and the pediatric group (Group II: ≤ 9.9 years). Group-I comprised of 18 patients and Group-II, 32 patients. Covered stent was implanted to 32 (73%) patients and uncovered stent to 12 (27%) patients. The procedural success rate was 100%. Following stent implantation, peak systolic gradient decreased significantly in both groups ( P  < .0001) (Group-I: from 35.9 ± 16.6 mm Hg–2.2 ± 3.4 mm Hg, Group II: from 34 ± 13.3 mm Hg–3 ± 4.09 mm Hg). Complications developed in 3 patients, and all in Group I. Femoral hematoma developed in 1 patient, balloon rupture occurred during the procedure in 1 patient, and there was temporary loss of pulse in 1 patient. All the complications were treated successfully. All the patients were taking anti-hypertensive drugs before intervention and during the mean 23-month follow-up period (range, 2–84 months), hypertension recovered in 35 (80%) patients and drugs were terminated. Stent implantation for aortic coarctation in the pediatric age group may provide pleasing results, reducing the coarctation gradient, providing effective dilatation in the lesion area and eliminating hypertension.